1978
DOI: 10.1288/00005537-197802000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Compound frontal sinus injuries with intracranial penetration

Abstract: Extensive trauma to the forehead, resulting in large penetrating wounds of the frontal sinus that extend into the frontal lobes of the brain, has traditionally been treated by frontal sinus ablation. Although this operation eliminates dead space, it leaves the patient with a depressed area in the forehead with little protection for the brain. The success of Nadell and Kline in replacing skull fragments following compound depressed skull fractures yet avoiding infection has spurred us to attempt this technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
3

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 12 publications
0
49
0
3
Order By: Relevance
“…Changes in mental status as well as nausea or vomiting are suggestive of intracranial injury. It is important to search for cerebrospinal fluid leakage from the nose or directly from lacerations and exposed bone which could signify dural displacement coupled with a posterior table fracture [2] (Figs. 1, 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in mental status as well as nausea or vomiting are suggestive of intracranial injury. It is important to search for cerebrospinal fluid leakage from the nose or directly from lacerations and exposed bone which could signify dural displacement coupled with a posterior table fracture [2] (Figs. 1, 2).…”
Section: Introductionmentioning
confidence: 99%
“…1, 2). A traumatic CSF fistula of the frontal sinus is a life threatening process deserving urgent attention [2].…”
Section: Introductionmentioning
confidence: 99%
“…In our diagnostic assessment we used an easy to apply classification (anterior and posterior plates of the frontal sinus, comminuting fracture and related injuries), suggested by Luce (1987) 7 and Donald (1982) 18 . Although being simple, this classification allows us to separate the cases with the greatest potential for complications (posterior plate lesions), which require more complex surgical procedures and medical care, from those which may be managed through simpler surgical approaches, such as the fractures involving the anterior plate of the frontal sinus 3,11,15,21,20 . We believe that clinical observation, supported by ancillary exams (endoscopy, radiographies, CT scans and MRI) shall guide the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In less severe injuries, the anterior plate protects the posterior, and the former is usually affected alone. The great impact injuries affect both the plates and the floor with bone fragmentation and derrangement [11][12][13] . By studying craniofacial trauma, Nahum 14 showed that the impact force necessary to cause a frontal sinus fracture is of 360 to 990 Kg (800 to 2,200lb), what is enough to cause other head injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation